Behçet’s disease in pregnancy: a case report and literature review - Xiangyue Li; Xuemei Huang; Xiaolan Yu (BMC Pregnancy and Childbirth)
Abstract Background Behçet’s disease (BD) during pregnancy is a relatively rare condition, and there are currently no established guidelines for its management. The effects of BD on both mothers and children remain unclear. In this paper, we present the diagnostic and treatment processes for a patient with BD during pregnancy. Case presentation A 20-year-old woman, gravida 2, para 1, presented to our inpatient department with recurrent oral and genital ulcers at 28 weeks and 3 days of gestation. Given the complexity of the patient’s condition, we initiated the first multidisciplinary consultation to establish appropriate treatment regimens. However, the initial treatment was ineffective, and the patient experienced a fever for four days. Consequently, we conducted a second multidisciplinary consultation. The final treatment regimen included azithromycin, hydroxychloroquine, prednisone, and low-molecular-weight heparin calcium. The clinical symptoms resolved, and the female neonate was delivered successfully. No relapse was observed during the four-month follow-up. Conclusions The critical issues in treatment involve ensuring medication safety for pregnant women and preventing adverse pregnancy outcomes. Notably, one potential cause of adverse pregnancy outcomes in individuals with BD is vasculopathy, which necessitates prompt treatment with anticoagulant therapy. Obstetricians should closely monitor disease progression and remain vigilant for complications in order to minimize adverse outcomes during pregnancy.